Alterations in the Peritoneal Fluid Proteome of Horses with Colic Attributed to Ischemic and Non-Ischemic Intestinal Disease - Rebecca C. Bishop; Justine V. Arrington; Pamela A. Wilkins; Annette M. McCoy (Animals)
Peritoneal fluid (PF) is intimately associated with the gastrointestinal tract, and changes in the PF may directly reflect abdominal pathology. We aimed to quantify differences in the PF proteome between intestinal lesion type (ischemic vs. non-ischemic) and location (small vs. large intestine). PF samples were collected at hospital admission from horses presenting for abdominal pain (colic). Cases were clinically categorized by lesion type and location after resolution (10 per group). PF proteins were extracted and quantified by label-free liquid chromatography-tandem mass spectroscopy. Data were analyzed in Perseus and R, with functional annotation by UniProtKB and interaction visualization in STRING. Sixteen proteins unique to ischemic lesions and twelve unique to small intestinal lesions had significant network enrichment with functions related to inflammatory and immune responses. Identified proteins related to ischemic and small intestinal lesions included calprotectin, lactotransferrin, alpha 2 macroglobulin, and serine proteases/protease inhibitors, as well as apolipoprotein B and lipid metabolism pathways not previously described in relation to ischemic intestinal disease. While no single biomarker is expected to adequately diagnose or predict the outcome of equine colic, the proteins identified here should be considered as candidates for further study in a larger population.